Electronic Liveworksheet- Based LKS Teaching Materials for Middle School Science Learning - Syahria Fardinelly; Adeng Slamet; Rahmi Susanti (Journal of Educational Sciences, 2024)
This study aims to analyze the needs of electronic student worksheets (LKPD) in junior high school (SMP) science learning. The population in this study was all eighth-grade students, totaling 30 people. The research was conducted using a qualitative-descriptive research approach by conducting an analysis at SMPIT Bina Ilmi. The results of the needs analysis of the use of liveworksheet-based LKPD in science subjects are as follows: 53.70% of students have difficulty understanding the digestive system material in science subjects in class VIII SMP. A live worksheet is one of the variations of teaching materials or learning media that can be used in the classroom. Based on the results of this needs analysis, the author's suggestion is that, based on the results of the analysis of students' needs for LKPD, E-LKPD is needed to increase students' interest in the learning process.